RANTAI NILAI PADA INDUSTRI SUSU STUDI KASUS PT CISARUA MOUNTAIN DAIRY (CIMORY) - Reza Satrya Arjakusuma; Sri Hartoyo; Idqan Fahmi (Jurnal Manajemen & Agribisnis, 2013)
ABSTRACTThe purpose of this study were to 1) map the value chain of Cimory, 2) analyze value chain governance in Cimory, 3) identify the barriers in Cimory value chain, 4) analyze the production efficiency in Cimory suppliers, and 5) identify the best strategy to upgrade the Cimory’s value chain so it can minimize any hindrance. This research used descriptive method that used value chain analysis, value chain governance analysis, barrier of production efficiency identification, and upgrading strategy. Based on value chain analysis, there are six actors in the whole Cimory value chain: KUD Giri Tani and KUD Cipanas as the dairy suppliers, Kiva Citra as the sugar supplier, Inopec as the bottle supplier, Cimory itself, Macrosentra Niagaboga as the main distributor, Cimory resto, Giant, Indomaret, Alfamart, Home Delivery, and Cimory agent. The relationship between Cimory and the main supplier is captive, between Cimory and secondary supplier is modular, and between Cimory and the distributor is more likely modular. The results of barriers identification showed that almost all barriers came from the main suppliers. The results from the production efficiency showed that only the working hour that didn’t have any positive effect for production. The prioritized strategy that needs to be done based on the upgrading analysis is improving the quality of fresh milk supplied to Cimory.Keywords: cimory, production efficiency, upgrading strategy, value chain, value chain analysis ABSTRAKPenelitian ini bertujuan 1) memetakan rantai nilai dari Cimory, 2) analisis pengelolaan rantai nilai dari Cimory, 3) mengidentifikasi berbagai hambatan pada rantai nilai Cimory, 4) analisis efisiensi produksi dari supplier Cimory, dan 5) identifikasi strategi yang tepat untuk meminimalisir hambatan yang dialami oleh Cimory. Penelitian ini bersifat penelitian deskriptif dengan menggunakan analisis rantai nilai, analisis pengelolaan rantai nilai, identifikasi hambatan, efisiensi produksi, dan strategi pengembangan. Hasil analisis rantai nilai terdapat enam aktor dalam rantai nilai Cimory secara keseluruhan: KUD Giri Tani dan KUD Cipanas sebagai pemasok susu segar, Kiva Citra sebagai pemasok gula, Inopec sebagai pemasok botol, Cimory, Macrosentra Niagaboga sebagai distributor utama, resto Cimory, Giant, Indomaret, Alfamart, Layanan pesan antar dan agen Cimory. Hubungan diantara Cimory dan pemasok utama bersifat captive, Cimory dan pemasok sekunder bersifat modular, dan hubungan dengan distributor lebih bersifat modular. Hasil dari identifikasi hambatan menunjukkan bahwa hampir semua hambatan berasal dari pemasok utama. Hasil dari efisiensi produksi menunjukkan hanya jam kerja yang tidak memiliki efek positif terhadap tingkat produktivitas. Strategi prioritas yang perlu dilakukan untuk melakukan peningkatan ialah dengan cara meningkatkan kualitas dari susu segar yang dipasok ke Cimory.Kata kunci: cimory, efisiensi produksi, strategi pengembangan, rantai nilai, analisis rantai nilai